The relationship between childhood emotional abuse and borderline personality disorder: the mediating role of difficulties in emotion regulation among Lebanese adults - Gaelle Kanj; Souheil Hallit; Sahar Obeid (Borderline Personality Disorder and Emotion Dysregulation, 2023)
Abstract Objective The present study investigates the mediating effect of difficulties in emotion regulation in the association between childhood emotional abuse and Borderline Personality Disorder (BPD) among Lebanese adults. Method This cross-sectional study, involving 411 participants, was conducted between March and August 2022. Lebanese individuals from all governorates of the country were recruited using the Snowball Sampling technique. Three self-report scales were utilized to complete this research; the ‘Difficulties in Emotion Regulation Scale—Brief Version (DERS-16)’ which evaluates the difficulties in emotion regulation of individuals, the ‘Childhood Trauma Questionnaire—Short Form (CTQ-SF)’ which grants a subjective evaluation of the general childhood environment of the participants, as well as the ‘Borderline Personality Questionnaire (BPQ)’ which measures Borderline Personality Disorder traits, that demonstrate significant convergence with the disorder. Results The results indicate that DERS-16 played an indirect effect role between childhood emotional abuse scores and Borderline Personality Disorder. Higher emotional abuse scores were significantly associated with higher DERS-16 scores, which in turn was significantly associated with higher BPQ scores. Moreover, childhood emotional abuse was directly associated with higher BPQ scores. Conclusion This work suggests that, among the different forms of childhood abuse, emotional abuse may have a role in the development of Borderline Personality Disorder. Training on emotion regulation strategies would potentially benefit individuals in preventing BPD development and facilitating therapeutic processes.